Development Of Character Education Teaching Materials Pemmali Cultural Values Based At Sambelia State 1 Elementary School - Zarkasi, Zarkasi; Sapri, Sapri (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2021)
Internalization of character values in each student should start early and be carried out continuously. The problem is that the inculcation of these values, specifically in Negeri 1 Sambelia Elementary Schoo, is not enough if only done in conventional ways. In reality, there are still many students who come to school late, do not complete assignments on time, and their participation rate in completing group work is very low. For this purpose, a model for internalizing character education is offered through the diffusion of cultural values from the surrounding community, which in this context is the pemmali culture of the residents of Sambelia Village, East Lombok Regency. The method used in formulating this idea is a study or library research. This idea contains an innovation in the form of a model of teaching materials by internalizing character values in students, especially in elementary schools through the cultural values of Pemmali. In more detail, it contains ways to find out the acceptance of Pemmali culture as learning content, types of Pemmali culture that can actually be internalized to students, various character values that can be internalized to students contained in Pemmali culture, and steps for internalization to students. educate.